On-surface synthesis approach to preparing one-dimensional organometallic and poly-p-phenylene chains. (7th September 2016) - Zhou, Xiong; Bebensee, Fabian; Shen, Qian; Bebensee, Regine; Cheng, Fang; He, Yang; Su, Hui; Chen, Wei; Xu, Guo Qin; Besenbacher, Flemming; Linderoth, Trolle R.; Wu, Kai
Abstract : Substrates and extrinsic metals on top dictate the reaction intermediates and pathways of on-surface Ullmann couplings. Abstract : On-surface Ullmann coupling reactions of dibromo-biphenyl and diiodo-biphenyl molecules on Ag(111), Cu(111), Au(111) and Au(100) and by deposited extrinsic Ag and Ni atoms were systematically explored. Poly- p -phenylene polymer chains turned out to be the final coupling products. Different organometallic polymer chains, [–Ph2 Ag–] n, [–Ph2 Cu–] n, and [–Ph2 Ni–] n, were synthesized as stable intermediates during the coupling reactions. These intermediates were confirmed and verified by X-ray photoelectronic spectroscopy, scanning tunnelling spectroscopy and tip manipulations. On Au surfaces, coupling products were achieved directly from halogenated precursors without formation of the Au-containing organometallic intermediates. Magnetic organometallic polymer chains were prepared by Ullmann coupling of dibromo-biphenyl activated by extrinsic Ni atoms on Au(100) surface and were confirmed by Kondo resonance measurement. Such an on-surface preparation strategy may provide an efficient approach to preparing unentangled organometallic and pure organic polymer chains and subsequently measuring their properties at surfaces.